Հայագիտության արդի վիճակը ՀՀ-ում և զարգացման հիմնախնդիրները - Սուվարյան, Յուրի Մ․ (ՀՀ ԳԱԱ հրատ.)
More than 10 years have passed since the first International Assembly on Armenian Studies was convened in Yerevan by the RA Academy of Sciences and the State University of Yerevan on September 15-20, 2003. The Assembly was an important event for highlighting and evaluating the development of Armenian Studies as an historical process, consolidating the domestic and foreign scholarly potentials, as well as securing their unhindered interaction in the future. Рассматривая арменоведение как одно из важнейших направлений государственной политики, правительство РА определило стратегию развития арменоведения РА на 2012-2025 гг. Была утверждена “Концепция развития арменоведения”, основан международный журнал “Вестник арменоведения” «Բանբեր հայագիտության» (на 5 языках), учрежден Международный совет, координирующий арменоведческие исследования.
Keywords: Պատմություն